Digital Game in Young Children's Numeracy Skill: An Innovation through Learning Media Development - Syarfina Syarfina; Siti Masruroh; Nur Masyitah; Yulia Sahpitri; Aulia Desi Pratiwi (Universitas Nahdlatul Ulama Surabaya, 2023)
Children's numeracy skills significantly influence their readiness to enter primary school. However, teaching numeracy to children in concrete periods is still a big challenge for teachers. Moreover, technologybased learning media must still be considered appropriate for early introduction. This research aims to develop an interactive digital learning media to improve early childhood numeracy skills. This Research and Development (RD) method used the 4-D model, which consists of Defining, Designing, Developing, and Disseminating. Expert validators who test the feasibility of the product consist of material, media, and language experts. Respondents in this study were ten children aged 4-5 years at PAUD Nurul Aisyah, East Aceh. The results showed that this digital game is feasible as a learning media to improve early childhood numeracy skills. The average validator score for product feasibility is in the very good category, and children's numeracy skills are in the good category. With this learning media, "Numb Game," children learn the concepts of counting, grouping, and simple statistics. Through an interactive approach, the development of Numb Game media can stimulate children's engagement in the numeracy learning process by utilizing visual elements, games, and interactions that stimulate curiosity and desire to understand mathematical concepts. Therefore, this interactive digital learning media presents an interesting, adaptive, and effective learning experience according to children's needs in improving numeracy skills at an early age. Further research on the long-term effects of using digital learning media on the development of early childhood numeracy skills and the implications for their academic achievement is warranted.